2013
DOI: 10.1007/s10585-013-9570-0
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 treatment of oral cancer induces epithelial-mesenchymal transition and promotes bone invasion via enhanced activity of osteoclasts

Abstract: This study investigates relationships between EMT and bone invasion by OSCC. Three OSCC cell lines, SCC25, HN5, and Tca8113 were artificially induced to display EMT by adding 5 ng/mL of TGF-β1 to culture media for 1–3 days. Cell morphology and phenotypic changes was examined by immunocytochemical staining of CK and VIM. EMT markers, cell-invasion factors, and osteoclast-related molecules were analysed at mRNA, gelatine and protein levels by real-time PCR, gelatine zymography and Western blotting respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 35 publications
2
46
0
4
Order By: Relevance
“…66,67 Transforming growth factor b (TGFb) can be produced by tumor-associated fibroblasts 68 and induce NF-jB activation 69 and SMAD-dependent MMP production, 70 as well as epithelial to mesenchymal transition (EMT) factors, such as Snail and Slug. [71][72][73][74][75][76] Invasion is stimulated by hypoxia in a Notch-dependent fashion. 77 Inhibition of Notch can also suppress MMP production.…”
Section: Cell Surface Receptors Influence Invasivementioning
confidence: 99%
“…66,67 Transforming growth factor b (TGFb) can be produced by tumor-associated fibroblasts 68 and induce NF-jB activation 69 and SMAD-dependent MMP production, 70 as well as epithelial to mesenchymal transition (EMT) factors, such as Snail and Slug. [71][72][73][74][75][76] Invasion is stimulated by hypoxia in a Notch-dependent fashion. 77 Inhibition of Notch can also suppress MMP production.…”
Section: Cell Surface Receptors Influence Invasivementioning
confidence: 99%
“…The mechanism that allows the invasion of neoplastic epithelial cells into adjacent connective tissue has been associated with the expression of cytokines, such TGF-ß 28,45 . Hwang et al 46 suggested that TGF-ß1…”
Section: Crosstalk Of the Molecules Involved In The Signaling Pathwaymentioning
confidence: 99%
“…This facilitates neoplastic cellular invasion with a more aggressive growth phenotype. In oral cancer, TGF-ß1 deregulation promotes EMT 28,45,47,48 . This is why studies focused on EMT and its relationship in carcinogenesis have increased recently.…”
Section: Crosstalk Of the Molecules Involved In The Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Transforming growth factor-β1 (TGF-β1) is a potent cytokine and bone-derived factor that is the founding member of the TGF-β superfamily (11). TGF-β1 is secreted by platelets, macrophages, and many other cell types, and exerts various biological effects, including cell cycle regulation, proliferation, differentiation, maturation, and apoptosis or immune activity, through binding to cell surface receptors and initiating intracellular signalling cascades (12).…”
mentioning
confidence: 99%